Adding Ajax - Powers, Shelley (O'Reilly, 2007)
"This book demonstrates many advantages of adding Ajax to enhance, rather than replace, the way your application works. Perhaps you have a traditional Web application based on submitting a form to update a table. You can enhance it by allowing users to update the table with changes to the form fields, without actually having to submit the form. That's just one example. Adding Ajax is for those of you who are more interested in extending existing applications than in creating Rich Internet Applications. You already know the business-side of applications - Web forms, server-side driven pages, and static content - and now you want to make your Web pages livelier, more fun, and much more interactive."--Jacket